2002
DOI: 10.1039/b106918g
|View full text |Cite
|
Sign up to set email alerts
|

Electroregenerable anion-exchange resin with triiodide carbon paste electrode for the voltammetric determination of adrenaline

Abstract: An electroregenerable carbon paste electrode modified with triiodide ions immobilized in an anion-exchange resin (Lewatit M500) is proposed for the determination of adrenaline in pharmaceutical products by differential-pulse voltammetry (DPV). Adrenaline was chemically converted into adrenochrome by the I3- ions at the electrode surface. The electrochemical reduction back to adrenaline was obtained at a potential of -0.16 V vs. Ag/AgCl (3 mol l(-1) KCl). A 20% decrease of the initial analytical signal was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…41 Lupetti et al used anionexchange resin with a triiodide carbon paste electrode for the determination of adrenaline. 42 To the best of our knowledge, no study has been reported on the electroanalysis and simultaneous determination of AA, AC and Trp using a modied graphite paste electrode with LFOR. This paper introduces for the rst time a simple method for the preparation of a new modied graphite paste electrode based on LFOR dispersed in paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…41 Lupetti et al used anionexchange resin with a triiodide carbon paste electrode for the determination of adrenaline. 42 To the best of our knowledge, no study has been reported on the electroanalysis and simultaneous determination of AA, AC and Trp using a modied graphite paste electrode with LFOR. This paper introduces for the rst time a simple method for the preparation of a new modied graphite paste electrode based on LFOR dispersed in paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…Also, IP should not be administered to patients with myocardial ischemia. Several methods have been described in the literature for the determination of IP such as flow injection spectrophotometry [3], ultra-performance liquid chromatography/timeof-flight mass spectrometry [4], and capillary electrophoresis [5]. Due to the advantages of relatively low cost, fast response, simple instrumentation, high sensitivity, facile miniaturization, and low power requirement, numerous voltammetric methods have been developed for the determination of IP [2, [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the immobilization of triiodide ion (I 3 -), the resin conversion was carried out in a glass column, as described previously [23] and shown in Figure 2.…”
Section: Immobilization Of Triiodide Ion (I 3 -) In the Ionexchange Resinmentioning
confidence: 99%